Hungary's Cold War : international relations from the end of World War II to the fall of the Soviet Union - Békés, Csaba (The University of North Carolina Press, 2022)
"In this magisterial and pathbreaking work, Csaba Békés shares decades of his research to provide a sweeping examination of Hungary's international relations with both the Soviet Bloc and the West from the end of World War II to the dissolution of the Soviet Union in 1991. Unlike many studies of the global Cold War that focus on East-West relationships--often from the vantage point of the West--Békés grounds his work in the East, drawing on little-used, non-English sources"-- Provided by publisher.
Keywords: Cold War.; Hungary -- Foreign relations -- Communist countries.; Communist countries -- Foreign relations -- Hungary.; Hungary -- Foreign relations -- Europe, Western.; Europe, Western -- Foreign relations -- Hungary.; Hungary -- Foreign relations -- United States.; United States -- Foreign relations -- Hungary.; Guerre froide.; Hongrie -- Relations extérieures -- Pays socialistes.; Pays socialistes -- Relations extérieures -- Hongrie.; Hongrie -- Relations extérieures -- Europe de l'Ouest.; Europe de l'Ouest -- Relations extérieures -- Hongrie.; Hongrie -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- Hongrie.; HISTORY / Europe / Eastern; Diplomatic relations; Communist countries; Hungary; United States; Western Europe; Politics & government.; Politics and Government.; Electronic books.